The role of national values in spiritual and moral education of students-youth. - Ismoilova Gulbakhor Azamovna; Muxammedova Mohichexra Baxodir qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article discusses the role of national values in the spiritual and moral education of the reader-youth, threats and risks under the guise of “ideological war”, “popular culture”.